Study on generation of attosecond pulse with polarization gating - Ghimire, Shambhu (Kansas State University, 2007)
It is still a dream to image the dynamics of electrons in atoms and molecules experimentally. This is due to the fact that such motion takes place in an ultra-short time scale; for example, an electron moves around the Bohr orbit in about 150-as (1 as = 10 -18 s), and pulses much shorter than this limit are not currently available to probe such fast dynamics. In recent years, an isolated single attosecond pulse has been produced by extracting the cutoff of harmonic spectrum driven by a laser pulse as short as ~ 5fs (1fs =10-15 s). But, these pulses are still too long in order to make the dream come true. Here, we study the possibility of generation of a much shorter and wavelength tunable single attosecond pulse by using polarization gating. In the experiment, we compressed ~30fs pulses from the laser amplifier down to ~6fs and characterized them. These linearly polarized pulses were converted to ellipticity varying pulses, and by exploiting the property of the strong dependence of the harmonic signal with the ellipticity of the laser, an XUV supercontinuum was produced in the harmonic spectrum which could support 60-as pulses. The bandwidth of such a supercontinuum, and therefore the duration of the attosecond pulses, is limited mainly by the currently available energy of the driving laser pulses at few cycle limits. In this project, we present an approach which allowed us to scale up the energy of such pulses by a factor of 1.5 in “Hollow Core Fiber / Chirped Mirrors Compressor”. Finally, in order to temporarily characterize the attosecond pulses we designed and built an “Attosecond Streak Camera”. Most of such cameras to date are limited to measuring a 1 dimensional energy spectrum and have only a few degrees of acceptance angle. Our camera is capable of measuring 2d momentum of the photoelectrons with large acceptance angle, for example ~ 65o at the photoelectron of energy ~15 eV. Recently, we observed the sidebands in addition to the main peaks in their laser assisted XUV photoelectron spectrum. The single attosecond pulses, after being characterized with this high speed camera, can be used to explore the dynamics of electrons at the attosecond scale.
Keywords: Attosecond; Ultrafast Laser; Higher order harmonic generation; Polarization gating; Physics, Atomic (0748)